Genome-wide association study identifies 32 novel breast cancer susceptibility loci from overall and subtype-specific analyses - Zhang, Haoyu; Ahearn, Thomas U.; Lecarpentier, Julie; Barnes, Daniel; Beesley, Jonathan; Jiang, Xia; O’Mara, Tracy A.; Qi, Guanghao; Zhao, Ni; Bolla, Manjeet K.; Dunning, Alison M.; Dennis, Joe; et al. (Cold Spring Harbor Laboratory, 2019)
AbstractBreast cancer susceptibility variants frequently show heterogeneity in associations by tumor subtype. To identify novel loci, we performed a genome-wide association study (GWAS) including 133,384 breast cancer cases and 113,789 controls, plus 18,908 BRCA1 mutation carriers (9,414 with breast cancer) of European ancestry, using both standard and novel methodologies that account for underlying tumor heterogeneity by estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) status and tumor grade. We identified 32 novel susceptibility loci (P<5.0×10-8), 15 of which showed evidence for associations with at least one tumor feature (false discovery rate <0.05). Five loci showed associations (P<0.05) in opposite directions between luminal- and non-luminal subtypes. In-silico analyses showed these five loci contained cell-specific enhancers that differed between normal luminal and basal mammary cells. The genetic correlations between five intrinsic-like subtypes ranged from 0.35 to 0.80. The proportion of genome-wide chip heritability explained by all known susceptibility loci was 37.6% for triple-negative and 54.2% for luminal A-like disease. These findings provide an improved understanding of genetic predisposition to breast cancer subtypes and will inform the development of subtype-specific polygenic risk scores.